The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1111/j.1751-0813.1980.tb05669.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Selenium Nutrition of Sheep in Victoria

Abstract: The selenium nutrition of sheep throughout Victoria was assessed by a survey of the blood glutathione peroxidase activity in 708 flocks. It was shown that the blood glutathione peroxidase activity in sheep had a seasonal variation with lowest levels in the spring. The enzyme activity was correlated with the blood selenium concentration. Areas where blood selenium was less than 0.03 micrograms/ml in spring were defined. Sheep with low selenium nutrition were grazing pastures in the high rainfall areas on acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Direct effects of cyanide on Se metabolism have been recorded in sheep (Rudert & Lewis 1978;Gutzwiller 1993), rats (Beilstein & Whanger 1984), and chicks (Elzubeir & Davis 1988). The seasonal occurrence of symptoms of Se deficiency in stock has been associated with periods of active clover growth (Underwood 1966;McDonald & Caple 1977;Caple et al 1980). It is not known if this association is solely the result of the low Se content of clover herbage, which is lower than browntop, cocksfoot, or ryegrass (Davies & Watkinson 1966), or if the cyanide released by clover markedly reduced absorption and utilisation of ingested Se.…”
Section: Resultsmentioning
confidence: 99%
“…Direct effects of cyanide on Se metabolism have been recorded in sheep (Rudert & Lewis 1978;Gutzwiller 1993), rats (Beilstein & Whanger 1984), and chicks (Elzubeir & Davis 1988). The seasonal occurrence of symptoms of Se deficiency in stock has been associated with periods of active clover growth (Underwood 1966;McDonald & Caple 1977;Caple et al 1980). It is not known if this association is solely the result of the low Se content of clover herbage, which is lower than browntop, cocksfoot, or ryegrass (Davies & Watkinson 1966), or if the cyanide released by clover markedly reduced absorption and utilisation of ingested Se.…”
Section: Resultsmentioning
confidence: 99%
“…It is principally when Se supplements are fed to Se-deficient cows that production responses can be expected. Witchel et al (1994) suggested cows grazing pasture with less than 30 g of Se/kg of DM would have inadequate Se intakes, whereas Caple et al (1980) considered that pasture with 50 g of Se/kg of DM would provide adequate Se. The Se concentrations in our pastures and supplements were always greater than 60 g of Se/kg of DM, indicating sufficiency of Se in the basal diet.…”
Section: Discussionmentioning
confidence: 99%
“…Binnerts (1979) reported milk Se concentrations of 3 to 5 g of Se/kg of milk from cattle in low-Se areas in the Netherlands and 6 to 11 g/kg for those from high-Se areas. Variations in Se concentrations in pastures (10 to >50 g of Se/kg of DM; Caple et al, 1980) may lead to variations in concentrations in milk, but the effects are likely to be relatively small unless significant amounts of Se are added in fertilizer (Aro et al, 1998). The Se concentrations in concentrate supplements, such as wheat (1 to 117 g/ kg of DM) and lupins (10 to 488 g/kg of DM), vary to a greater degree than those in pasture (White et al, 1981) and are therefore more likely to affect concentrations in milk.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of average GSH-Px activity within the experimental period cannot be explained by an analytical failure as the levels were rechecked later from freezed samples. A seasonal variation in blood GSH-Px activity in sheep has been reported (CAPLE et al, 1980). Thc seasonal variation in the present study could partly arise from changcs in oxidative processes contributed by vitamin E. However, the effect of vitamin E on GSH-Px activity has been reported to vary between species and in lambs it has been shown to have no effect on this selenoenzyme (GODWIN et al, 1975).…”
Section: Discussionmentioning
confidence: 46%